Effects of biotic interactions on tropical tree performance depend on abiotic conditions. Issue 12 (28th November 2018) - Muscarella, Robert; Messier, Julie; Condit, Richard; Hubbell, Stephen P.; Svenning, Jens‐Christian
Abstract: Predicting biotic responses to environmental change requires understanding the joint effects of abiotic conditions and biotic interactions on community dynamics. One major challenge is to separate the potentially confounding effects of abiotic environmental variation and local biotic interactions on individual performance. The stress gradient hypothesis (SGH) addresses this issue directly by predicting that the effects of biotic interactions on performance become more positive as the abiotic environment becomes more stressful. It is unclear, however, how the predictions of the SGH apply to plants of differing functional strategies in diverse communities. We asked (1) how the effect of crowding on performance (growth and survival) of trees varies across a precipitation gradient, and (2) how functional strategies (as measured by two key traits: wood density and leaf mass per area, LMA) mediate average demographic rates and responses to crowding across the gradient. We built trait‐based neighborhood models of growth and survival across a regional precipitation gradient where increasing precipitation is associated with reduced abiotic stress. In total, our dataset comprised 170, 000 individual trees belonging to 252 species. The effect of crowding on tree performance varied across the gradient; crowding negatively affected growth across plots and positively affected survival in the wettest plot. Functional traits mediated average demographic rates across the gradient, but we did not find clear evidence that the strength of these responses depends on species' traits. Our study lends support to the SGH and demonstrates how a trait‐based perspective can advance these concepts by linking the diversity of species interactions with functional variation across abiotic gradients.